O agostinismo político: contribuições e limites para as discussões políticas medievais - Souza, Luciano Daniel de [UNESP] (2014)
This study was carried out to analyze Henri-Xavier Arquillière's political Augustinism (1883-1956), in order to understand the historical moment in which he formulated that historical category for the medieval politics. For Arquillière, Saint Augustin's political thought was inverted in its fundamental aspects propitiating interpretive versions. Aquillière, French historian, argued in 1934 that the political thought followed by Gregorius VII and other Popes was based on the political Augustinism. According to Aquillière, the political Augustinism was contested on the basis that it was a neoThomist and apologetical version of the papacy 's actions. Within that context, one tried to understand whether the assertions on Saint Augustin's importance might be relegated due to its institutional connection with the author. Certeau, in his conception about the social role played by the historian, contributes to such a thesis pointing out that every historian starts from an institution which assigns legitimacy and authenticity to his/her historiography. Such a thesis is unfolded, at first, in order to know Aquillière's academic background, historiography, and textbooks. The French historian, by disclosing features of the methodical school, expanded the political Augustinism as an explanatory reading of medieval politics thus exposing himself to generalization problems. Aquillière wrote textbooks in which he introduced political Augustinism to young people aiming at explaining his teachings on the Catholic Church, redeeming its importance in the political and religious background of his time. By analyzing A Cidade de Deus, one notices in Saint Augustin's writings benevolent attitudes toward the Roman Empire and the lack of assertions which gave support to a papal monarchy. NeoThomism at the time Aquillière formulated the political Augustinism was an active movement within the Catholic Church, it allowed a careful examination of Augustinian ...